Discovering the healthcare beliefs and practices of rural mestizo Ecuadorians. An ethnonursing study - A. Moss, Julie (Investigación y Educación en Enfermería, 2014)
Objetive. To discover and understand the healthcare beliefs and practices of mestizo Ecuadorians within rural Ecuador. Methodology. An ethnonursing method developed by Leininger was used to guide this study and four phases of qualitative data analysis. 28 informants were interviewed in Tosagua, Ecuador. Results. Data analysis revealed four themes (a) Spirituality and prayer necessary for health and well-being, (b) Sharing life with people positively affects health and well-being, (c) Incorporation of both traditional and modern medicine is essential to health (d) Environmental context beyond the control of the people greatly affect health and well-being. Conclusion. The findings are consistent with the cultural life ways of rural mestizo Ecuadorians who live in community with one another. These results can be used to enable nurses and other healthcare workers to provide care that is acceptable, culturally congruent and promotes health in rural Ecuador.